2011
DOI: 10.1073/pnas.1103012108
|View full text |Cite
|
Sign up to set email alerts
|

Limited or no protection by weakly or nonneutralizing antibodies against vaginal SHIV challenge of macaques compared with a strongly neutralizing antibody

Abstract: To guide vaccine design, we assessed whether human monoclonal antibodies (MAbs) b12 and b6 against the CD4 binding site (CD4bs) on HIV-1 gp120 and F240 against an immundominant epitope on gp41 could prevent vaginal transmission of simian HIV (SHIV)-162P4 to macaques. The two anti-gp120 MAbs have similar monomeric gp120-binding properties, measured in vitro, but b12 is strongly neutralizing and b6 is not. F240 is nonneutralizing. Applied vaginally at a high dose, the strongly neutralizing MAb b12 provided steri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
251
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(266 citation statements)
references
References 44 publications
13
251
0
2
Order By: Relevance
“…Il est cependant à noter que l'importance des mécanismes d'inhibition dépendants des RFc a d'ores et déjà été confirmé dans des modèles animaux [11,18,19]. En effet, dans un modèle de primate non humain, l'étude du transfert passif de l'anticorps neutralisant b12 ou de l'anticorps b12 mutant (dénommé LALA et incapable de fixer le complément ou les RFcγ) a démontré une diminution de 50 % de l'efficacité de protection par l'anticorps LALA [11,18].…”
Section: Les Anticorps Non Neutralisants Inhibiteurs In Vivounclassified
See 1 more Smart Citation
“…Il est cependant à noter que l'importance des mécanismes d'inhibition dépendants des RFc a d'ores et déjà été confirmé dans des modèles animaux [11,18,19]. En effet, dans un modèle de primate non humain, l'étude du transfert passif de l'anticorps neutralisant b12 ou de l'anticorps b12 mutant (dénommé LALA et incapable de fixer le complément ou les RFcγ) a démontré une diminution de 50 % de l'efficacité de protection par l'anticorps LALA [11,18].…”
Section: Les Anticorps Non Neutralisants Inhibiteurs In Vivounclassified
“…Plus récemment, une fonction de protection partielle et une activité sur la diminution de la charge virale ont été attribuées à des Ac non neutralisants inhibiteurs dans le modèle de primate non humain. Ces anticorps possèdent des fonctions inhibitrices dépendantes de leur région Fc et de l'expression des RFc [19,20]. Chez les patients infectés, des anticorps inhibiteurs sont fréquemment détectés très tôt après la phase aiguë de l'infection ( Figure 1, courbe rouge) [21,22].…”
Section: Les Anticorps Non Neutralisants Inhibiteurs In Vivounclassified
“…52 Additional support for this possibility comes from a recent study in the rhesus macaque SHIV model of HIV-infection. Burton et al 43 demonstrated that a non-neutralizing Ab clone directed against the gp41 component of the HIV Env can mediate limited protection against SHIV challenge in rhesus macaques.…”
Section: Repertoire Freeze and Selection Of Bnabs And Other Protectivmentioning
confidence: 99%
“…40 These Abs are seen as ideal candidates for an effective HIV vaccine to induce, as upon passive transfer to rhesus macaques and vector-induced expression in humanized mice they protect from infection with SHIV and HIV, respectively. [41][42][43][44][45] Despite the attractiveness of these targets for vaccines and the considerable interest they have invoked, attempts to induce BnAbs through vaccination have failed. The impediment to stimulating BnAbs through vaccination is, at least in part, thought to be related to the extensive somatic hypermutation required to generate these Abs.…”
Section: Utilizing Idiotypic Repertoire Freeze To Maintain Vaccine Inmentioning
confidence: 99%
“…For example, potential conflicts of priorities between treatment and prevention may arise, and emergence of escape mutants could compromise available therapy options (6,7). Human anti-HIV-1 broadly neutralizing monoclonal antibodies (bnMAbs) may provide attractive options in this context, given their proven protective efficacy against infection upon pre-and/or postexposure uses in animal challenge models (8)(9)(10)(11)(12)(13)(14) and inherent general safety because of their human origin. A phase I randomized controlled clinical trial has been recently completed for a vaginal microbicide candidate containing three bnMAbs, 2F5, 4E10, and 2G12, showing that daily vaginal administration of the bnMAbs (50 mg each) to healthy women for 12 days was safe and well tolerated (15).…”
mentioning
confidence: 99%